Incidence of Colorectal Carcinoma in Rectal Bleeding Patients - Hasan, Md Kamrul; Barman, Biplab Kumar; Faysal, Md Abu Bakar Siddiq; Debnath, Joyanti Rani; Sultana, Sunia; Islam, Md Faridul (Medicine Today, 2026)
Introduction: In Bangladesh there is no complete data which would reflect the idea about the incidence of colorectal carcinoma in rectal bleeding patients. Nowadays the incidence of colorectal carcinoma is increasing day by day. The number of patient attending physician are increasing day by day due to increased consciousness, improved health care facility and availability of more advanced investigative tools. Rectal bleeding is one of the commonest symptoms which is commonly diagnosed and managed in the surgery department. This study is designed to evaluate the incidence as well as diagnosis of colorectal carcinoma in rectal bleeding patients in the surgery department. Aims and Objective: To evaluate the rectal bleeding patients attending outdoor and indoor in surgery department in Cu M C H. Study the incidence of colorectal carcinoma in rectal bleeding patients. Methods: All patients who presented with rectal bleeding and consequently diagnosed as colorectal carcinoma by clinical examinations, colonoscopic evaluation and histopathological examination were analyzed prospectively. Sociodemographic data & results of laboratory investigations, findings on examination were noted. The patients of rectal bleeding who give consent were included. Patients who refused & patients less than 15 years, seriously ill patients were excluded. Results: Among the 250 patients studied, 18 of the patients were diagnosed as colorectal carcinoma and incidence was 7.2%, 58 patients(23.2%) were diagnosed as haemorrhoid, 20 patients(08%) had ulcerative colitis, 08 patients(3.2%) had ileocaecal TB, 06 patients(2.4%) had caecal ulcer, 10 patients(04%) had colonic polyp. Among 18 patients of colorectal carcinoma, 15 patients distributed ≥50 years (about 83.33%) and next was 21-49 years 3 patients (about 16.67%). 12 patients were male (66.67%) and 6 were female (33.33%). 13 patients were muslim (72.22%), 5 were hindu (27.78%). 10 patients (55.56%) came from urban areas, 8 patients (44.44%) came from rural area. Among 18 case of colorectal carcinoma,10 were in rectum (55.55%), 4 in sigmoid colon (22.22%), 3 in caecum (16.67%), 1 in transverse colon (5.56%). 4 patients had a family history of colorectal carcinoma (22.22%). Among 18 case of colorectal carcinoma all were adenocarcinoma (100%) on histological examination. Conclusion: Rectal bleeding is a common problem in our community. Overall the awareness and knowledge about this symptom is poor. This study is aimed at arousing consciousness as well as diagnosis of colorectal carcinoma who presented with rectal bleeding. Medicine Today 2026, Vol.38 (1): 65-70